Nanomaterials Mechanics and Mechanisms - Ramesh, K.T (Springer US : Imprint: Springer, 2009)
The enabling science in much of nanotechnology today is the science of nanomaterials; indeed in the broadest sense, nanotechnology would not be possible without nanomaterials. Nanomaterials: Mechanics and Mechanisms seeks to provide an entrè into the field for mechanical engineers, material scientists, chemical and biomedical engineers and physicists. The objective is to provide the reader with the connections needed to understand the intense activity in the area of the mechanics of nanomaterials, and to develop ways of thinking about these new materials that could be useful to both research and application. The book covers all of the fundamentals of the mechanical properties of materials in a highly readable style, and integrates most of the literature on the emerging field of nanomaterials into a coherent body of knowledge. This volume provides a basic understanding of mechanics and materials, and specifically nanomaterials and nanomechanics, in one self-contained text. Graduate and advanced undergraduate students will find well-organized chapters that provide the necessary background in mechanics, mechanical properties and modeling. The writing style illustrates concepts through quantitative modeling techniques, in contrast to theoretical abstractions of materials behavior. Problem sets within each chapter aim to motivate discussion and further study in this rich and bourgeoning field. Providing engineers with the knowledge necessary to take full advantage of the tremendous potential of nanomaterials, Nanomaterials: Mechanics and Mechanisms is a valuable teaching/learning tool for mechanical engineering, physics and materials science audiences.